HALL RESULTS ON UNCONTROLLED NATURAL CONVECTIVE FLOW OF MHD THROUGH AN IMPULSIVELY FLOWING PLATE WITH TEMPERATURE AND CONCENTRATION RAMPED - YATA PANDU, SATEESH DOPATI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this paper, we discuss heat transfer on the peristaltic magneto hydrodynamic flow of a Jeffrey fluid through a porous medium in a vertical echelon under the influence of a uniform transverse magnetic field normal to the channel, taking Hall current into account. This study is motivated towards the physical flow of blood in a microcirculatory system by taking account of the particle size effect. Here we consider the Reynolds number to be small enough and wavelength-to-diameter ratio large enough to neglect inertial effects. The nonlinear governing equations for the Jeffrey fluid are solved making use of the perturbation technique. The exact solutions for the velocity, temperature, and the pressure rise per one wavelength are determined analytically. Its behavior is discussed computationally with reference to different physical parameters. Some parameters are the strongest on the trapping bolus phenomenon and the pumping characteristics. The size of the trapping bolus decreases with increasing Hartmann number or permeability parameter and increases with increasing Hall parameter or Jeffrey number.